Mollugin reacts with phenol thiol but not produce modification on cysteine discovered by a phenol thiol probe - Liu, Tao; Qi, Ruibing; Feng, Wanshi; Li, Zhuohao; Zhong, Zerun; Bai, Chuan (Frontiers in Cell and Developmental Biology, 2025)
Electrophilic compounds from natural products (NPs) and metabolites can covalently modify the cysteines of target proteins to induce biological activities. To facilitate the discovery of novel NPs and metabolites, chemical probes with various thiol groups—mimicking the reactivity of cysteine—have been developed. These probes are designed to react with electrophilic groups of NPs and metabolites in an electrophilic addition mechanism, with the resulting adducts having molecular masses which equal to the sum of the probe and the target compound. This principle has been fundamental to analyzing mass spectrometry (MS) data and calculating the exact molecular weights of the target compound. In this study, we report a phenol thiol probe initially designed to mimic cysteine reacts with Mollugin and other structurally related NPs in an electrophilic free radical addition mechanism, and thus leads to the incorporation of not only the thiol probe but also a hydroxyl group in the adducts. Our results demonstrate that the phenol thiol group of the probe cannot always represent the thiol in cysteine to discover novel NPs or metabolites that can covalently modify cysteines.